Population attributable fractions of the main type 2 diabetes mellitus risk factors in women: Findings from the French E3N cohort. Issue 3 (23rd September 2018) - Rajaobelina, Kalina; Dow, Courtney; Romana Mancini, Francesca; Dartois, Laureen; Boutron‐Ruault, Marie‐Christine; Balkau, Beverley; Bonnet, Fabrice; Fagherazzi, Guy
Abstract: Background: Although many type 2 diabetes mellitus (T2DM) risk factors have been identified, little is known regarding their contributions to the diabetes burden at the population level. Methods: The study included 72 655 French women from the Etude Epidemiologique de Femmes de la Mutuelle Générale de l'Education Nationale (E3N) prospective cohort followed between 1993 and 2011. Cox multivariable models including the main T2DM risk factors (metabolic, dietary, clinical, socioeconomic and hormonal) and a healthy lifestyle index combining five characteristics (smoking, body mass index [BMI], alcohol consumption, fruit and vegetable consumption, and physical activity) were used to estimate hazard ratios and population attributable fractions (PAFs) for T2DM. Results: In multivariate models, factors with the strongest effect on T2DM risk were, in decreasing order, BMI ≥ 30 kg/m 2 (PAF = 43%; 95% confidence interval [CI] 37–47), high adherence to a Western dietary pattern (PAF = 30%; 95% CI 20–40), hypertension (PAF = 26%; 95% CI 20–32), an acidogenic diet (PAF = 24%; 95% CI 16–32), a family history of diabetes (PAF = 20%; 95% CI 17–22), and, with a negative correlation, moderate alcohol consumption (PAF–19%; 95% CI –34, −4). The PAF for an unhealthy lifestyle was 57% (95% CI 50–63). Conclusions: We have been able to sort out and quantify the effect of various dietary and biological T2DM risk factors simultaneously in a single population, and to highlight the importance of a healthy lifestyle for primary prevention: more than half the T2DM cases could have been prevented through a healthier lifestyle. Abstract : Highlights If all the women from the E3N study had followed a healthy lifestyle, 57% of cases of type 2 diabetes mellitus (T2DM) cases could have been prevented. This study helps sort out and quantify the effects of various dietary and biological T2DM risk factors, and highlights the importance of a healthy lifestyle for primary prevention. Clinicians could use these results to explain to their patients how lifestyle changes can directly affect their risks of developing T2DM.